Psychomotor education, an aspect of general formation of the pre-school children - Shingjergji, Ardian (Journal of Education Culture and Society, 2020)
Current developments of scientifi c thinking in the fi eld of education, are increasingly de-manding in various disciplines for young people as a matter of urgency. It is already known that child development is conditioned by ancestry, socio-cultural environment, including interaction with peers and adults. Albanian institutions (kindergarten) compared to contem-porary experience in more developed countries have to deal with issues such as: (1) The de-velopment of a run or optimal acceleration enrichment motor for kindergarten children, seen as an important element of the formation of the human personality and its preparation to cope with various situations of life ; (2) The role of infrastructure in the natural development of the personality of children and the educational process as a whole; (3) Parental community involvement as a fundamental prerequisite of real development of the child; (4) The qualifi -cation level of the teaching staff in the elementary education system and the preparation of students teacher. I hope to add my contribution through this paper, not only by identifying the problems abo-ve, but also in presenting alternatives of a development model of kindergarten children motors skills progress, compared to contemporary experience in more developed countries.